(untitled) (JURNAL ADMINISTRASI BISNIS, 2016)
ABSTRACK : Financial performance analysis band is used assessing business continuity, stability, profitability of any company. And each company will not be sparated from a variety of problems. The many problems that arise can not be resolved immediately. Analysis is required really precise and accurate. The method that band is used in this research uses in this research uses descriptive quantitative method. And ratio analysis profitability. And the result of this research is based on that; in 2013 a calculation using the ratio of profitability with gross profit margin formula : gross profit / net sales = 56%, net profit margin: net profit after tax / net sales = 41.57% the earning power of total investment: profit before tax / total assets = 26.64%, return on equity: profit after tax / shareholders equity = 16.91% and in 2014, gross profit margin: gross profit / net sales = 48.38% decrease the net profit margin: net profit after tax / net sales = 34.24% decrease compared to the year 2013, the earning power of the total investment: profit before tax / total assets = 72.87% an increase compared to 2013. Return on equity: profit after tax / shareholders equity = 14.28% decrease as well. And in 2015 , a decline in gross profit margin: gross profit / net sales = 37.30%. net profit margin: net profit after tax / net sales = 24.48% . earning power of the total investment: profit before tax / total assets = 46.83%. Return on equity: profit after tax / shareholders equity = 10.26% . compared to the year 2013 was not too decrease compared to 2014 and 2015 there is a decrease in income. Keywords: financial performance in the profit planning